STRATEGI PENGEMBANGAN OBJEK WISATA ISTANA BASA PAGARUYUNG DI KABUPATEN TANAH DATAR - Gustia Refnoliza; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes how the Developmen’t Strategy of Tourism Object Basa Pagaruyung Palace at Tanah Datar Recency. This study also look at the constraints faced by local governments in the development of tourism.The theory used in this study is the management strategy, in particular Lina and Lena theories, and to determine appropriate strategies to address the problem. On the issue of tourism in Tanah Datar required appropriate strategies to address the problems that exist to increase visits to the tourist sector revenue in developing regional tourism. This study used a qualitative approach with descriptive methods. Data collection techniques used through interviews, observation, and documentation as well as the selection of literary study with informants with snow ball sampling while the unit of analysis of this study is that the institution Department of Tourism Culture and Sports, as well as to test the validity of data trianglasi to check the degree of confidence behind a information.Based on the theory used for the analysis it can be concluded that the problems in setting the strategy for tourism development are yet to be adequately addressed, the Government only prioritize the development Pagaruyuang Palace which still continues today, so that there is a problem during the development of tourism be resolved. Such a strategy also has reason because of limited funds and the government itself does not have a master plan for the development of tourism to be more focused and able to compete with other regions so many investors are willing to cooperate with the Government of Tanah Datar, in addition to the cooperation between the government, the public, and also stake holders as executor in the field should cooperate with each other. In addition, Tanah Datar also does not have PHRI (Persatuan Hotel dan Restoran Indoesia) and ASITA (Asosiasi Tourisme Indonesia) to oversee the development of regional tourism in Tanah Datar.Keywords: Strategy, Tourism Development